2007
DOI: 10.1242/jeb.007096
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical basis of lingual hydrostatic deformation

Abstract: SUMMARY The mammalian tongue is believed to fall into a class of organs known as muscular hydrostats, organs for which muscle contraction both generates and provides the skeletal support for motion. We propose that the myoarchitecture of the tongue, consisting of intricate arrays of muscular fibers, forms the structural basis for hydrostatic deformation. Owing to the fact that maximal diffusion of the ubiquitous water molecule occurs orthogonal to the short axis of most fiber-type cells, diffusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
82
0
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 49 publications
3
82
0
3
Order By: Relevance
“…This study showed evidence of the tongue acting as a muscular hydrostat. 17,36 The area of the tongue grid in the sagittal plane was not different pre and post mandibular advancement. In a muscular hydrostat, the shape changes but the volume remains constant.…”
Section: Discussionmentioning
confidence: 91%
“…This study showed evidence of the tongue acting as a muscular hydrostat. 17,36 The area of the tongue grid in the sagittal plane was not different pre and post mandibular advancement. In a muscular hydrostat, the shape changes but the volume remains constant.…”
Section: Discussionmentioning
confidence: 91%
“…Thus an alternative mechanism is needed for these patients. The muscular hydrostat argument 17,18 may provide insight into this phenomenon, whereby the tongue maintains a constant volume (regardless of the forces acting on it ie, gravity, muscle activation). In this case, our data lead us to speculate that an enlarged tongue (thereby posteriorly located) has little space to move into (with position changes/muscle activation) regardless of whether supine or lateral.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian tongues, the intrinsic musculature typically includes transverse muscle fibers in alternating sheets of parallel muscle fibers oriented more or less vertically and horizontally and longitudinal muscle fibers in bundles around the central core of transverse muscle fibers. Mammalian tongue deformations and many types of tongue movement are generated according to the general principles outlined above for muscular hydrostats (Bailey and Fregosi, 2004;Gilbert et al, 2007;Kier and Smith, 1985;McClung and Goldberg, 2000;Napadow et al, 1999). Muscular-hydrostatic mechanisms may also be important in the support and movement of many lizard tongues and some frog tongues (Chiel et al, 1992;Nishikawa et al, 1999;Smith and Mackay, 1990;Smith, 1986;van Leeuwen, 1997;van Leeuwen et al, 2000;Wainwright and Bennett, 1992a;Wainwright and Bennett, 1992b).…”
Section: W M Kiermentioning
confidence: 99%